2020
DOI: 10.1148/radiol.2020200195
|View full text |Cite
|
Sign up to set email alerts
|

Feature Tracking of Global Longitudinal Strain by Using Cardiovascular MRI Improves Risk Stratification in Heart Failure with Preserved Ejection Fraction

Abstract: In total, 206 consecutive participants with HFpEF (mean age, 71 years 6 8 [standard deviation]; 69% women) were included. Median myocardial global longitudinal strain (GLS) at MRI was 28.5% and showed low correlation with extracellular volume (r = 0.28; P = .003). A total of 109 events (53%) were recorded during a follow-up of 38 months 6 29. Participants with a GLS above the median had higher event rates (log-rank test, P , .001). By multivariable Cox regression analysis, GLS remained independently associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 31 publications
3
37
0
Order By: Relevance
“…Our current analysis showed that CAD was independently associated with impaired GLS but not with GCS or GRS. This finding highlights the prognostic value of GLS in predicting cardiovascular events [ 25 ]. The association between CAD and impaired GLS in our study could provide evidence on why men appear more likely than women to have sudden cardiac death related to CAD [ 7 ].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our current analysis showed that CAD was independently associated with impaired GLS but not with GCS or GRS. This finding highlights the prognostic value of GLS in predicting cardiovascular events [ 25 ]. The association between CAD and impaired GLS in our study could provide evidence on why men appear more likely than women to have sudden cardiac death related to CAD [ 7 ].…”
Section: Discussionmentioning
confidence: 75%
“…In terms of HFpEF, strain analysis allows the detection of systolic dysfunction in the absence of an overt reduction in LVEF and shows prognostic value in predicting adverse outcomes [ 24 , 25 ]. However, available data regarding the sex-related impact of coexisting DM on LV contractility in patients with HFpEF remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure (HF) with preserved ejection fraction (HFpEF) is as prevalent as HF with reduced ejection fraction (HFrEF) [ 1 4 ]; the prognosis of HFpEF is poor, similar to that of HFrEF [ 1 , 5 ]. The prevalence of HFpEF will continue to increase as life expectancy increases [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…GLS can detect subtle changes in the myocardium after infarction, thereby more accurately assessing systolic function and providing additional prognostic information [21][22][23]. A considerable number of STEMI patients have undergone PCI, and their LVEF is close to normal or may even remain unchanged; consequently, they are considered low-risk patients [24].…”
Section: Discussionmentioning
confidence: 99%